Organic small molecule material taking triazine as core, preparation method of organic small molecule material and lithium ion battery
By designing triazine core organic small molecule materials with specific active sites, the problem of limited improvement in electrochemical performance of lithium-ion batteries is solved, higher capacity and cycle stability is achieved, and the application of other ion batteries is expanded to the application of other ion batteries. Flexible skeleton structure and diversity.
Patent Information
- Application Number
- CN202411174971.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-17
AI Technical Summary
The electrochemical performance of existing organic small molecule materials in lithium-ion batteries is limited, which can easily lead to problems such as low capacity, low Coulomb efficiency and poor circulation.
Using organic small molecule materials with triazine as the core, materials with carbonyl and carbon-nitrogen double bond redox active sites are designed by adjusting the number and connection methods of active groups, and prepared by specific synthetic methods, including triamino Tetrahydrofuran and water were dissolved in the triazine, hydrochloric acid and sodium nitrite were added, potassium iodide was added, and then reacted with potassium acetate and palladium catalysts to obtain an organic small molecule material with a flexible framework structure.
Improves the electrochemical performance of lithium-ion batteries, designability of materials and chemical structure diversity, and can be used in a variety of ion batteries, including lithium ions, sodium ions, potassium ions, etc., and is not restricted by embedded ions. It is suitable for flexibility or thin battery devices.
Smart Images

Figure CN119143685A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of organic optoelectronic materials, and in particular to an organic small molecule material with triazine as the core, a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Lithium-ion batteries (LIBs), as a new type of secondary battery with high energy density, high cycle times and long service life, are widely used in mobile power supplies, electric vehicles, home appliances, smart wearable devices, 3C products and other fields, and are gradually becoming the main power source for new energy vehicles and energy storage. With the increase in energy demand and the development of the new energy industry, lithium-ion batteries are facing new challenges in terms of energy density, power density and cost.
[0003] The designability and chemical structure diversity of organic materials allow researchers to construct new molecules and structures according to their needs. For example, the theoretical capacity and redox potential of the material can be regulated by introducing more active functional groups, changing the types of functional groups, and introducing corresponding substituents, thereby designing high-performance new organic electrode materials. For example, patent CN117024689B discloses an alkynyl-modified triazine ring covalent organic framework material and its preparation method, lithium-sulfur battery positive electrode, and lithium-sulfur battery. The triazine ring covalent organic framework material has the high crystallinity and porous structure of COFs two-dimensional honeycomb mesh, and contains an alkynyl functionalized ligand unit centered on the triazine ring.
[0004] At present, small molecule organic electrode materials have the advantages of abundant sources, simple synthesis, and low price, but they are usually easy to dissolve in organic electrolytes, which will cause the "shuttle effect", resulting in low capacity, low coulombic efficiency, and poor cyclability. Therefore, it is very necessary to provide an organic small molecule material that can effectively improve the electrochemical performance of lithium-ion batteries. Summary of the invention
[0005] The embodiment of the present application provides an organic small molecule material with triazine as the core, so as to solve the problem that the existing organic small molecule materials in the related art have limited improvement on the electrochemical performance of lithium-ion batteries.
[0006] The present application provides an organic small molecule material with triazine as the core, and its general structural formula is shown in Formula I:
[0007]
[0008] In Formula I, L 1 , L 2 , L 3 independently selected from single bonds, pyrazine, p-benzoquinone, Ar 1 ,Ar 2 ,Ar3 Independently selected from substituted or unsubstituted anthraquinone, substituted or unsubstituted phenanthrenequinone, substituted or unsubstituted pyrene-4,5,9,10-tetraone.
[0009] In some embodiments, the group Ar 1 ,Ar 2 ,Ar 3 Independently selected from the following groups:
[0010]
[0011] In some embodiments, the group Ar 1 ,Ar 2 ,Ar 3 Independently selected from the group
[0012] In a second aspect, the present application also provides a method for preparing the above-mentioned organic small molecule material with triazine as the core, comprising the following steps:
[0013] Step S101, adding tetrahydrofuran and water to triaminotriazine to dissolve, adding hydrochloric acid, ice bathing, then adding sodium nitrite, adding potassium iodide after the reaction, extracting, drying, filtering, concentrating, and column chromatography after the reaction is completed to obtain a first reaction product;
[0014] Step S102, mixing the first compound, the second compound, potassium acetate and the palladium catalyst, evacuating the mixture, filling the mixture with nitrogen, adding anhydrous N,N-dimethylformamide to dissolve the mixture, heating the mixture to react, and after the reaction is complete, cooling the mixture to room temperature, extracting, drying, filtering, concentrating and columnizing the mixture to obtain a second reaction product;
[0015] Step S103, the first reaction product, the second reaction product, potassium carbonate and palladium catalyst are mixed, vacuumed, filled with nitrogen, then toluene, ethanol and water are added to dissolve, heated for reaction, and after the reaction is completed, extracted, dried, filtered, concentrated and column-filtered to obtain the organic small molecule material S.
[0016] In a third aspect, the present application also provides a method for preparing an organic small molecule material with triazine as the core, comprising the following steps:
[0017] Step S101, adding tetrahydrofuran and water to triaminotriazine to dissolve, adding hydrochloric acid, ice bathing, then adding sodium nitrite, adding potassium iodide after the reaction, extracting, drying, filtering, concentrating, and column chromatography after the reaction is completed to obtain a first reaction product;
[0018] Step S102, mixing the first compound, the second compound, potassium acetate and the palladium catalyst, evacuating the mixture, filling the mixture with nitrogen, adding anhydrous N,N-dimethylformamide to dissolve the mixture, heating the mixture to react, and after the reaction is complete, cooling the mixture to room temperature, extracting, drying, filtering, concentrating and columnizing the mixture to obtain a second reaction product;
[0019] Step S103', mixing the second reaction product obtained in step S102 with the third compound, potassium carbonate, and palladium catalyst, evacuating and filling with nitrogen, adding toluene, water, and ethanol to dissolve, heating to react, and after the reaction is completed, cooling, extracting, drying, filtering, concentrating, and column-filtering to obtain a third reaction product;
[0020] Step S104', mix the third reaction product, the first reaction product, potassium carbonate and palladium catalyst, evacuate, fill with nitrogen, add toluene, water and ethanol to dissolve, heat to react, and after the reaction is completed, cool to room temperature, extract, dry, filter, concentrate, and pass through a column to obtain an organic small molecule material B.
[0021] In some embodiments, in step S102, the first compound is selected from a compound The second compound is selected from biboric acid pinacol ester; the heating reaction temperature is 65-85°C.
[0022] In some embodiments, in step S103, the heating temperature is 75-100°C.
[0023] In step S103', the third compound is selected from compound
[0024] In some embodiments, the palladium catalyst is selected from 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride or tetrakis(triphenylphosphine)palladium or palladium acetate.
[0025] In some embodiments, in steps S103 and S103', toluene and ethanol may be replaced by tetrahydrofuran.
[0026] In some embodiments, anhydrous N,N-dimethylformamide can be replaced with toluene.
[0027] In some embodiments, in steps S103' and S104', the heating temperature is 75-100°C.
[0028] In a fourth aspect, the present application provides a lithium-ion battery, wherein the positive electrode material of the lithium-ion battery includes the above-mentioned organic small molecule material S or organic small molecule material B.
[0029] The technical solution provided in the present application brings the following beneficial effects: (1) The organic small molecule material obtained in the present application has redox active sites of carbonyl (C=O) and carbon-nitrogen double bond (C=N). The theoretical capacity and solubility of the material can be adjusted by changing the number and connection mode of the active groups. The material has strong designability and chemical structure diversity, and new molecules and structures can be quickly constructed according to different needs; (2) The organic small molecule material provided in the present application has a flexible skeleton structure and can be used to produce flexible or thin battery devices; (3) The organic small molecule material provided in the present application is not limited by embedded ions. The same organic material can be used not only for LIBs, but also for other large-size alkali metal ion batteries (sodium ion and potassium ion batteries), non-metal ion batteries (proton batteries, ammonium ion batteries and anion storage, etc.), and even multivalent metal ion battery systems (zinc ion, magnesium ion, calcium ion and aluminum ion batteries), and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 A schematic diagram of the reaction process for preparing the organic small molecule material S1 in Example 1 of the present application;
[0032] Figure 2 A schematic diagram of the reaction process for preparing organic small molecule material S2 in Example 2 of the present application;
[0033] Figure 3 This is a schematic diagram of the reaction process for preparing organic small molecule material S3 in Example 3 of the present application. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0035] The embodiment of the present application provides an organic small molecule material with triazine as the core, which can solve the problem that the organic small molecule materials in the prior art have limited improvement on the electrochemical performance of lithium-ion batteries.
[0036] The general structural formula of the organic small molecule material with triazine as the core provided in the embodiment of the present application is shown in Formula I:
[0037]
[0038] In Formula I, L 1 , L 2 , L 3 independently selected from a single bond, -NH-, pyrazine, p-benzoquinone, Ar 1 ,Ar 2 ,Ar 3 Independently selected from substituted or unsubstituted anthraquinone, substituted or unsubstituted phenanthrenequinone, substituted or unsubstituted pyrene-4,5,9,10-tetraone.
[0039] Among them, the group Ar 1 ,Ar 2 ,Ar 3 Independently selected from the following groups:
[0040]
[0041] The organic small molecule material provided by the present application, its preparation method, and the lithium ion battery containing the same are described in detail below in conjunction with the embodiments.
[0042] Embodiment 1:
[0043] (1) Weigh compound A1 triaminotriazine (12.61 g, 100.0 mmol), add it to a 2000 mL three-necked round-bottom flask, add 200 mL of tetrahydrofuran and 400 mL of water to dissolve; add 4 mol / L HCl (375 mL, 1.5 mol), ice bath; add sodium nitrite (31.05 g, 450 mmol), react for 1 h, then add potassium iodide (119.52 g, 720 mmol), react overnight at room temperature; take a sample point plate, the raw material has reacted completely, pour the reaction system into water, extract with dichloromethane three times, dry the organic layer with anhydrous magnesium sulfate, filter, concentrate, and pass column chromatography to obtain compound B1 (37.17 g, 81 mmol), with a yield of 81%;
[0044] (2) Weigh compound C1 (14.35 g, 50.0 mmol), compound D1 biboric acid pinacol ester (31.74 g, 125 mmol), potassium acetate (24.54 g, 250 mmol), and catalyst 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride (732 mg, 1 mmol) into a 500 mL three-necked round-bottom flask, evacuate and fill with nitrogen three times, add 200 mL of anhydrous N,N-dimethylformamide to dissolve, heat to 80°C and react for 20 hours; take a sample point plate, the raw materials have reacted completely, cool the reaction system to room temperature, pour into water, extract three times with dichloromethane, dry the organic layer with anhydrous magnesium sulfate, filter, concentrate, and pass column chromatography to obtain compound E1 (14.35 g, 43 mmol), with a yield of 86%;
[0045] (3) Compound B1 (4.58 g, 10 mmol), compound E1 (11.02 g, 33 mmol), potassium carbonate (12.44 g, 90 mmol), and catalyst tetrakis(triphenylphosphine)palladium (1.73 g, 1.5 mmol) were weighed and added into a 250 mL three-necked round-bottom flask. The flask was evacuated and filled with nitrogen three times. 60 mL of toluene, 40 mL of water, and 20 mL of ethanol were added to dissolve the mixture. The mixture was heated to 95° C. and reacted for 12 hours. The sample point plate was taken and the raw materials had reacted completely. The reaction system was cooled to room temperature and poured into water. The mixture was extracted with dichloromethane three times. The organic layer was dried over anhydrous magnesium sulfate, filtered, concentrated, and subjected to column chromatography to obtain compound S1 (5.74 g, 8.2 mmol) with a yield of 82%.
[0046] The reaction process of each compound in Example 1 is shown in Figure 1 The structural formulas of compound A1, compound B1, compound C1, compound E1 and compound S1 are shown in Figure 1 .
[0047] Embodiment 2:
[0048] (1) Preparation of compound B1: The preparation process is the same as that of Example 1;
[0049] (2) Compound C2 (23.79 g, 100.0 mmol), compound D1 biboric acid pinacol ester (152.36 g, 600.0 mmol), potassium acetate (94.21 g, 960 mmol), and catalyst 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride (7.32 g, 10 mmol) were weighed and added into a 1000 mL three-necked round-bottom flask, and the mixture was evacuated and filled with nitrogen three times. 600 mL of anhydrous N,N-dimethylformamide was added to dissolve the mixture, and the mixture was heated to 80° C. and reacted for 20 hours. The sample point plate was taken, and the raw materials had reacted completely. The reaction system was cooled to room temperature, poured into water, and extracted with dichloromethane three times. The organic layer was dried over anhydrous magnesium sulfate, filtered, concentrated, and subjected to column chromatography to obtain compound E2 (27.88 g, 84 mmol) with a yield of 84%.
[0050] (3) Compound E2 (16.60 g, 50.0 mmol), compound C3 (17.05 g, 50.0 mmol), potassium carbonate (20.73 g, 150 mmol), and catalyst tetrakis(triphenylphosphine)palladium (1.15 g, 1.0 mmol) were weighed and added to a 500 mL three-necked round-bottom flask, and the mixture was evacuated and filled with nitrogen three times. 150 mL of toluene, 100 mL of water, and 50 mL of ethanol were added to dissolve the mixture, and the mixture was heated to 95° C. and reacted for 12 hours. The sample point plate was taken, and the raw materials had reacted completely. The reaction system was cooled to room temperature, poured into water, and extracted with dichloromethane three times. The organic layer was dried over anhydrous magnesium sulfate, filtered, concentrated, and subjected to column chromatography to obtain compound E3 (16.78 g, 36.0 mmol) with a yield of 72%.
[0051] (4) Compound B1 (4.58 g, 10 mmol), compound E3 (15.39 g, 33 mmol), potassium carbonate (12.44 g, 90 mmol), and catalyst tetrakis(triphenylphosphine)palladium (1.73 g, 1.5 mmol) were weighed and added into a 250 mL three-necked round-bottom flask. The flask was evacuated and filled with nitrogen three times. 60 mL of toluene, 40 mL of water, and 20 mL of ethanol were added to dissolve the mixture. The mixture was heated to 95° C. and reacted for 12 hours. The sample point plate was taken and the raw materials had reacted completely. The reaction system was cooled to room temperature and poured into water. The mixture was extracted with dichloromethane three times. The organic layer was dried over anhydrous magnesium sulfate, filtered, concentrated, and subjected to column chromatography to obtain compound S2 (9.54 g, 8.7 mmol) with a yield of 87%.
[0052] The reaction process of each compound in Example 2 is shown in Figure 2 The structural formulas of compound C2, compound E2, compound C3, compound E3 and compound S2 are shown in Figure 2 .
[0053] Embodiment 3:
[0054] (1) Preparation of compound B1: The preparation process is the same as that of Example 1;
[0055] (2) Compound C4 (26.59 g, 100.0 mmol), compound D1 biboric acid pinacol ester (152.36 g, 600.0 mmol), potassium acetate (94.21 g, 960 mmol), and catalyst 1,1'-bis(diphenylphosphino)ferrocene palladium dichloride (7.32 g, 10 mmol) were weighed and added into a 1000 mL three-necked round-bottom flask, and the mixture was evacuated and filled with nitrogen three times. 600 mL of anhydrous N,N-dimethylformamide was added to dissolve the mixture, and the mixture was heated to 80° C. and reacted for 20 hours. The sample point plate was taken, and the raw materials had reacted completely. The reaction system was cooled to room temperature, poured into water, extracted three times with dichloromethane, and the organic layer was dried over anhydrous magnesium sulfate, filtered, concentrated, and subjected to column chromatography to obtain compound E4 (29.88 g, 83 mmol) with a yield of 83%.
[0056] (3) Compound E4 (18.00 g, 50.0 mmol), compound C5 (17.25 g, 50.0 mmol), potassium carbonate (20.73 g, 150 mmol), and catalyst tetrakis(triphenylphosphine)palladium (1.15 g, 1.0 mmol) were weighed and added to a 500 mL three-necked round-bottom flask, and the mixture was evacuated and filled with nitrogen three times. 150 mL of toluene, 100 mL of water, and 50 mL of ethanol were added to dissolve the mixture, and the mixture was heated to 95° C. and reacted for 12 hours. The sample point plate was taken, and the raw materials had reacted completely. The reaction system was cooled to room temperature, poured into water, and extracted with dichloromethane three times. The organic layer was dried over anhydrous magnesium sulfate, filtered, concentrated, and subjected to column chromatography to obtain compound E5 (18.43 g, 37.0 mmol) with a yield of 74%.
[0057] (4) Compound B1 (4.58 g, 10 mmol), compound E5 (16.44 g, 33 mmol), potassium carbonate (12.44 g, 90 mmol), and catalyst tetrakis(triphenylphosphine)palladium (1.73 g, 1.5 mmol) were weighed and added into a 250 mL three-necked round-bottom flask. The flask was evacuated and filled with nitrogen three times. 60 mL of toluene, 40 mL of water, and 20 mL of ethanol were added to dissolve the mixture. The mixture was heated to 95° C. and reacted for 12 hours. The sample point plate was taken and the raw materials had reacted completely. The reaction system was cooled to room temperature and poured into water. The mixture was extracted with dichloromethane three times. The organic layer was dried over anhydrous magnesium sulfate, filtered, concentrated, and subjected to column chromatography to obtain compound S3 (9.77 g, 8.2 mmol) with a yield of 82%.
[0058] The reaction process of each compound in Example 3 is shown in Figure 3 The structural formulas of compound C4, compound E4, compound C5, compound E5 and compound S3 are shown in Figure 3 .
[0059] S1 to S3 were respectively applied to the positive electrode active materials in lithium-ion batteries, button-type lithium batteries were assembled, and electrochemical performance tests were performed. The specific process is as follows:
[0060] Weigh PVDF (mass concentration 5%, 100 mg) in a homogenization box, add compounds S1-S3 (30 mg) and conductive carbon black SP (15 mg) respectively, put the homogenization box into a homogenizer for homogenization, and adjust the fluidity and solid content of the slurry by adding solvent N-methylpyrrolidone (NMP) during this process. After the slurry is completely dispersed, use a 200um scraper to coat it on aluminum foil, put the electrode into a vacuum drying oven and dry it at 120°C for 12 hours, cut and weigh the electrode, put it into a vacuum drying oven again and dry it at 80°C for 12 hours, and weigh it again. When the difference in the mass of the electrode weighed twice can be ignored, it indicates that the electrode has been completely dried. Finally, CR2032 button cells were assembled in a glove box filled with argon atmosphere (water and oxygen less than 0.1 ppm), and the assembly order was positive electrode shell-positive electrode sheet-diaphragm-lithium sheet-gasket-spring-negative electrode shell. The electrolyte used was 1MLiTFSI (volume ratio of DME / DOL = 1:1), and the separator was celgard 2400. The electrochemical properties of the button cells were as follows:
[0061] The specific capacity of the button cell corresponding to S1 is 254 mAh / g. After 1000 cycles (current density 100 mA / g), the capacity retention rate is 72%.
[0062] The specific capacity of the button cell corresponding to S2 is 458 mAh / g, and after 1000 cycles (current density 100 mA / g), the capacity retention rate is 76%. The specific capacity of the button cells corresponding to compounds S1 and S2 is less than that of compound S3. The applicant analyzed that this is because the active units of compounds S1 and S2 are less than that of compound S3.
[0063] The specific capacity of the button cell corresponding to S3 is 687 mAh / g. After 1000 cycles (current density 100 mA / g), the capacity retention rate is 85%.
[0064] In the description of this specification, the description with reference to the terms "one embodiment / method", "some embodiments / methods", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment / method or example are included in at least one embodiment / method or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment / method or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments / methods or examples. In addition, those skilled in the art may combine and combine the different embodiments / methods or examples described in this specification and the features of the different embodiments / methods or examples, unless they are contradictory.
[0065] It should be noted that, in the present application, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprise one..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically stipulated.
[0066] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. An organic small molecule material with triazine as the core, characterized in that: The general structural formula of the organic small molecule material is shown in Formula I: In formula I, L1, L2, and L3 are independently selected from a single bond, pyrazine, and para-benzoquinone, and Ar1, Ar2, and Ar3 are independently selected from substituted or unsubstituted anthraquinone, substituted or unsubstituted phenanthrenequinone, and substituted or unsubstituted pyrene-4,5,9,10-tetraone.
2. The organic small molecule material with triazine as the core according to claim 1, characterized in that: The groups Ar1, Ar2, and Ar3 are independently selected from the following groups:
3. The organic small molecule material with triazine as the core according to claim 1, characterized in that: The groups Ar1, Ar2, and Ar3 are independently selected from the group 4. The method for preparing the organic small molecule material with triazine as the core according to any one of claims 1 to 3, characterized in that: The following steps are involved: S101, adding tetrahydrofuran and water to triaminotriazine to dissolve, adding hydrochloric acid, ice bathing, then adding sodium nitrite, adding potassium iodide after the reaction, extracting, drying, filtering, concentrating, and column chromatography after the reaction is completed to obtain a first reaction product; S102, mixing the first compound, the second compound, potassium acetate and the palladium catalyst, evacuating the mixture, filling the mixture with nitrogen, adding anhydrous N,N-dimethylformamide to dissolve the mixture, heating the mixture to react, and after the reaction is complete, cooling the mixture to room temperature, extracting, drying, filtering, concentrating and columnizing the mixture to obtain a second reaction product; S103, mixing the first reaction product, the second reaction product, potassium carbonate and palladium catalyst, evacuating the mixture, filling with nitrogen, then adding toluene, ethanol and water to dissolve, heating to react, and after the reaction is completed, extracting, drying, filtering, concentrating and column-filtering to obtain an organic small molecule material S.
5. The method for preparing an organic small molecule material with triazine as the core according to claim 4, characterized in that: The method comprises: step S103', mixing the second reaction product obtained in step S102 with the third compound, potassium carbonate and palladium catalyst, evacuating and filling with nitrogen, adding toluene, water and ethanol to dissolve, heating to react, and cooling, extracting, drying, filtering, concentrating and column-passing after the reaction is completed to obtain the third reaction product; S104', mixing the third reaction product, the first reaction product, potassium carbonate and palladium catalyst, evacuating and filling with nitrogen, adding toluene, water and ethanol to dissolve, heating to react, and after the reaction is completed, cooling to room temperature, extracting, drying, filtering, concentrating and column-passing to obtain the organic small molecule material B.
6. The method for preparing an organic small molecule material with triazine as the core according to claim 4, characterized in that: The molar ratio of triaminotriazine to potassium iodide is 1:7-8; in step S102, the first compound is selected from compound The molar ratio of the first compound to the second compound is 1:6-7; the second compound is selected from diboric acid pinacol ester; the heating reaction temperature is 65-85°C.
7. The method for preparing an organic small molecule material with triazine as the core according to claim 4, characterized in that: In step S103, the molar ratio of the first reaction product to the second reaction product is 1:3-4; and the heating temperature is 75-100°C.
8. The method for preparing an organic small molecule material with triazine as the core according to claim 5, characterized in that: In step S103', the third compound is selected from compound The molar ratio of the second reaction product to the third compound is set to 1:1-2; in steps S103' and S104', the heating temperature is 75-100°C; the molar ratio of the third reaction product to the first reaction product is 1:3-4.
9. The method for preparing an organic small molecule material with triazine as the core according to claim 5, characterized in that: The palladium catalyst is selected from 1,1'-bis(diphenylphosphino)ferrocenepalladium dichloride or tetrakis(triphenylphosphine)palladium or palladium acetate.
10. A lithium ion battery, characterized in that: The positive electrode material of the lithium-ion battery comprises an organic small molecule material prepared by the preparation method described in claim 4 or claim 5.
